Integrasi Asas Legalitas dan Asas Oportunitas: Suatu Kajian Komparatif terhadap Penerapannya dalam Praktik Penuntutan - Muhammad; Akhmad Munawar; Hanafi (CV Rewang Rencang, 2023)
The integration of the legality principle and the opportunity principle in prosecutorial practice in Indonesia is a complex issue that requires in-depth study. The legality principle, which demands legal certainty, often clashes with the opportunity principle, which grants prosecutors discretion in decision-making. This study analyzes the dynamics of the interaction between these two principles through a literature review and case studies. The findings indicate challenges in achieving a balance between the two, particularly in defining the boundaries of prosecutorial authority and objective criteria for applying the opportunity principle. The study concludes that there is a need for regulatory improvements, increased transparency, and effective oversight mechanisms to ensure that the application of the opportunity principle does not deviate from the principles of justice and legal certainty.